New perspectives on Middle East politics : economy, society, and international relations - Mason, Robert, 1979- (Political economy and international relations of the Middle East., 2021)
"This compelling volume examines important and cross-cutting themes in the study of contemporary Middle East and North African politics and international relations. Drawing together contributions from scholars based within the region and beyond, it weaves together essential interdisciplinary, conceptually rich, and forward-looking content. Chapters cover population and youth, civil-military relations, soft power and geopolitical competition, regionalization and internationalization of conflict, the role of oil in reconstruction efforts, extra-regional actors, environmental politics, and specifically, the Israel-Palestine conflict. Students are supported with an extended and innovative glossary, including key concepts, actors and abbreviations. New Perspectives on Middle East Politics serves as an ideal primer and companion volume for scholars of Middle East Studies, as well as for policy professionals, journalists and the general reader engaging and re-engaging with the region."--